A proposal for the secondary structure of a variable area of eukaryotic small ribosomal subunit RNA involving the existence of a pseudoknot. - Neefs, J M (1990)
Eukaryotic small ribosomal subunit RNAs contain an area of variable structure, V4, which comprises about 250 nucleotides in most species, whereas the corresponding area in bacterial small ribosomal subunit RNAs consists of about 64 nucleotides folded into a single hairpin. There is no consensus on the secondary structure of area V4 in eukaryotes, about 10 different models having been proposed. The prediction of a model on a comparative basis poses special problems because, due to the variability of the area in length as well as sequence, a dependable alignment is very difficult to achieve. A new model was derived by systematic examination of all combinations of helices that have been hitherto proposed, plus some new ones. The following properties of the helices were examined: transposability to all presently known sequences, presence of compensating substitutions, and thermodynamic stability. A model was selected by ranking all possible combinations of transposable helices according to the number of compensating substitutions scored. The optimal model comprises a pseudoknot and four hairpin structures. Certain species contain additional hairpins inserted between these structural elements, while in others the structure is partially or entirely deleted.